Relationship between economic growth, corruption and global competitiveness in 20 Latin American countries and their Integration Agreements (2019)
This is a work that analyzes the macroeconomic perspectives of the Latin American region, which focuses on 20 countries, on the role of economic growth, corruption and competitiveness, within a time frame of 11 years, which includes the period between 2007 and 2017 The database has become a more solid basis for making growth decisions. besides to knowing how these variables are related in the regional integration procedures. © 2019.